The big food view and human health from the prospect of bio-manufacturing and future food - Wang, Jing; Zhang, Xin (Frontiers in Nutrition, 2023)
The “big food view” has attracted widespread attention due to the view of sustainable nutrition and human health as part of sustainable development. The “big food view” starts from better meeting the people's needs for a better life. While ensuring the supply of grain, the effective supply of meat, vegetables, fruits, aquatic products and other foods also should be guaranteed. Using cell factories to replace the traditional food acquisition methods, establishing a new model of sustainable food manufacturing, will greatly reduce the demand for resources in food production, and improve the controllability of food production and manufacturing, and effectively avoid potential food safety and health risks. Cell factories can provide key technologies and supporting methods for the biological manufacturing of important food components, functional food ingredients and important functional nutritional factors, realizing a safer, nutritious, healthy and sustainable way of food acquisition. The combination of cell factory technology and other technologies meets the people's new dietary demand, and also supports that sustainable nutrition and human health as part of sustainable development. This paper focuses on the big food view and human health from the prospect of bio-manufacturing and future food, which aims to better meet people's dietary needs for increasingly diversified, refined, nutritious and ecological food through diversified food manufacturing.